2011
DOI: 10.1038/ijo.2011.231
|View full text |Cite
|
Sign up to set email alerts
|

Learning about the energy density of liquid and semi-solid foods

Abstract: BACKGROUND: People learn about a food's satiating capacity by exposure and consequently adjust their energy intake. OBJECTIVE: To investigate the effect of energy density and texture on subsequent energy intake adjustments during repeated consumption. DESIGN: In a randomized crossover design, participants (n ¼ 27, age: 21 ± 2.4 years, body mass index: 22.2 ± 1.6 kg m À2) repeatedly consumed highly novel foods that were either low-energy-dense (LE: 30 kcal per 100 g) or high-energy-dense (HE: 130 kcal per 100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In 16 studies 17 , 18 , 25 , 50 , 52 , 53 , 55 58 , 61 66 , manipulations of food forms that were included consisted of liquid versus solid or liquid versus semi-solid or semi-solid versus solid, and included chunky and pureed food. Food consisted mainly of vegetables, fruit, meat and beverage (fruit juices) and texture was manipulated by blending the food.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 16 studies 17 , 18 , 25 , 50 , 52 , 53 , 55 58 , 61 66 , manipulations of food forms that were included consisted of liquid versus solid or liquid versus semi-solid or semi-solid versus solid, and included chunky and pureed food. Food consisted mainly of vegetables, fruit, meat and beverage (fruit juices) and texture was manipulated by blending the food.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies measured food texture instrumentally, of which 14 assessed viscosity 17 , 20 22 , 24 , 29 , 55 , 56 , 59 62 , 64 , 67 , two measured lubricity indirectly by measuring friction coefficients 29 , 60 , one measured foam volume as a function of time 54 and one used aperture sieving 19 . Eleven studies assessed food texture using sensory evaluation, of which three studies have used a trained panel (11, 29, 33 panellists) 20 , 29 , 52 , four studies untrained (20, 20, 24, 32 panellists) 26 , 27 , 51 , 62 , and in two studies it is unclear whether it was a trained or untrained panel (20 panellists) 21 , 53 . Two studies did not publish or did not show the data 25 , 66 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24). However, a recent review by Yeomans showed that studies investigating this phenomenon show mixed results [25].…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies demonstrated adaptation (i.e. loss of a reported initial effect) in EI (17,27,28). Of these, only Wanders 2014 (17) also measured appetite and found the acute obesity reviews effects of treatment on appetite endured.…”
Section: Energy Intakementioning
confidence: 98%